2009
DOI: 10.1590/s0080-62342009000600010
|View full text |Cite
|
Sign up to set email alerts
|

Anemia em gestantes de municípios das regiões Sul e Centro-Oeste do Brasil

Abstract: We aimed to analyze anemia distribution in pregnant women who were attending health services in two cities in the South and Mid-West Regions in Brazil. This is a retrospective cross-sectional study developed from 954 and 781 medical records data in Cuiabá-MT and Maringá-PR. We collected data of social and demographic features as well as pre-natal care. Women who presented hemoglobin lower then 11g/dL were considered having anemia. Social inequity between the two cities was evident. Pregnant women from Cuiabá-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
10

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 12 publications
0
15
0
10
Order By: Relevance
“…6,11 Whereas prevalence was moderate in the North, Northeast, and Central-West regions, prevalence in the South and Southeast was low. Mean Hb levels were also significantly higher in the post-fortifi cation group, both for the sample as a whole and for the Northeast, North, and Southeast regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,11 Whereas prevalence was moderate in the North, Northeast, and Central-West regions, prevalence in the South and Southeast was low. Mean Hb levels were also significantly higher in the post-fortifi cation group, both for the sample as a whole and for the Northeast, North, and Southeast regions.…”
Section: Discussionmentioning
confidence: 99%
“…Although it affects all social strata and geoeconomic areas, it is associated with inadequate social and environmental conditions. 3,11 Pregnant women are especially susceptible to iron defi ciency anemia due to the increased iron requirements associated with rapid expansion of fetal tissues and production of red blood cells. 20 The World Health Organization (WHO) estimates that over half the pregnant women in developing countries are anemic, while in developed countries anemia affects around one-quarter of pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to categories of epidemiological importance, they are classified as mild, a level defined by prevalences of anemia in pre-school children and pregnant women ranging between 5% and 20%, according to the classification proposed by the World Health Organization (WHO) 1 . A recent study developed in the semi-arid region of the state of Alagoas found a prevalence of 50% of anemia in pregnant women 18 , while the prevalence observed in primary health units in the city of Cuiabá was 25.5% 19 , revealing a result that was very different from that found in Maringá. Thus, researchers confirmed the alarming results of anemia found by the PNDS 5 in women of childbearing age, which affects 39% of this population in the Northeast region.…”
Section: Discussionmentioning
confidence: 73%
“…Os outros 6 estudos selecionados [19][20][21][22][23][24][25] foram realizados em gestantes atendidas em UBS por participantes do projeto intitulado "Perspectivas da fortificação das farinhas de trigo e de milho com ferro no controle da anemia 2006/2007".…”
Section: Resultsunclassified